2005
DOI: 10.1111/j.1365-294x.2005.02735.x
|View full text |Cite
|
Sign up to set email alerts
|

Colour vision and speciation in Lake Victoria cichlids of the genus Pundamilia

Abstract: Lake Victoria cichlids are one of the most speciose groups of vertebrates. Selection on coloration is likely playing an important role in their rapid speciation. To test the hypothesis that sensory biases could explain species differences in mating preferences and nuptial coloration, we studied seven populations of four closely related species of the genus Pundamilia that differ in visual environment and male nuptial colour. Microspectrophotometry determined that the wavelength of maximum absorption (lambdamax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
213
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 159 publications
(222 citation statements)
references
References 61 publications
9
213
0
Order By: Relevance
“…For instance, the females of two sympatric species of Lycaena butterflies appear to use wing colour to identify conspecific males and their visual pigments are well matched to facilitate such discriminations (Bernard & Remington 1991). The coloration of cichlid fish is believed to play a role in speciation (Seehausen & von Alphen 1998;Couldridge & Alexander 2001) and there is some evidence that their spectral sensitivities match their nuptial coloration (Carleton et al 2005). Reproductive isolation in fiddler crabs may be aided by their species-specific coloration, but whether their colours evolved in response to a pre-existing sensory bias or drove the evolution of the visual pigments is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the females of two sympatric species of Lycaena butterflies appear to use wing colour to identify conspecific males and their visual pigments are well matched to facilitate such discriminations (Bernard & Remington 1991). The coloration of cichlid fish is believed to play a role in speciation (Seehausen & von Alphen 1998;Couldridge & Alexander 2001) and there is some evidence that their spectral sensitivities match their nuptial coloration (Carleton et al 2005). Reproductive isolation in fiddler crabs may be aided by their species-specific coloration, but whether their colours evolved in response to a pre-existing sensory bias or drove the evolution of the visual pigments is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Species-specific colours, like those common in fiddler crabs (Crane 1975), may influence the evolution of visual pigments (Goldsmith 1991;Endler 1992) and vice versa (Endler 1992;Ryan & Keddy-Hector 1992;Ryan 1998;Carleton et al 2005). For instance, the females of two sympatric species of Lycaena butterflies appear to use wing colour to identify conspecific males and their visual pigments are well matched to facilitate such discriminations (Bernard & Remington 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Male cichlids exhibit very vivid colors during the mating season (their nuptial colors) that are specific to a given species and are likely to serve as signals to help females identify mates of the right species. It turns out that photopigments can be very different in different species, suggesting that the eyes of individuals of the different species are specifically "tuned" to see the nuptial colors of the males from their species (Carleton et al 2005). Behavioral studies that examine female mating preferences have shown that when you mask the color differences between males in the laboratory by using monochromatic light, the females show no preference between their own males and those of a closely related species (Mann et al 2004).…”
Section: Color Vision and Sexual Selection In Cichlidsmentioning
confidence: 99%
“…Variation in light environments within a habitat causes associated changes in sensed colour signal parameters [1][2][3][4][5]. This results from interactions among the spectral composition of light (relative light intensity at each wavelength or 'colour'), the total intensity of light, the medium through which light travels to the eye, and the surrounding visual backgrounds.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the received signal can be different under different light environments, altering the perceived conspicuousness of a colour pattern. Visual spectral sensitivities [2,3] also change in response to the predominant light environment, causing changes in signal perception that can result in long-term changes in colour patterns [4]. These processes can lead to polymorphism, population divergence, or speciation [3,5,6].…”
Section: Introductionmentioning
confidence: 99%